2018
DOI: 10.1039/c8ra06330c
|View full text |Cite
|
Sign up to set email alerts
|

One-dimensional chain structures of hexanuclear uranium(iv) clusters bridged by formate ligands

Abstract: Three one-dimensional chain structures of uranium(iv) hexanuclear clusters have been synthesized under hydrothermal/solvothermal conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 38 publications
1
7
0
Order By: Relevance
“…Indeed, to the best of our knowledge, only one other U­(IV) glutarate phase has been reported in the solid state, and it consists of a ligand-decorated hexamer . In fact, the hexamer is the most widely reported polynuclear species in actinide­(IV) structural chemistry and has been isolated with a wide variety of ligands including simple monocarboxylates (formate, acetate, chloroacetate, glycine) ,,, and polycarboxylates ,,, (terephthalates, fumarate, DOTA). Interestingly, in U-3 , the difunctional ligands result in the propagation of the hexanuclear entities into an extended three-dimensional network.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, to the best of our knowledge, only one other U­(IV) glutarate phase has been reported in the solid state, and it consists of a ligand-decorated hexamer . In fact, the hexamer is the most widely reported polynuclear species in actinide­(IV) structural chemistry and has been isolated with a wide variety of ligands including simple monocarboxylates (formate, acetate, chloroacetate, glycine) ,,, and polycarboxylates ,,, (terephthalates, fumarate, DOTA). Interestingly, in U-3 , the difunctional ligands result in the propagation of the hexanuclear entities into an extended three-dimensional network.…”
Section: Resultsmentioning
confidence: 99%
“…Yet, using the adipate, the U 6 clusters are instead linked into 1D chains, likely due to the increased flexibility of the six-carbon adipate as compared to succinate. To the best of our knowledge, such ligand-bridged one-dimensional chains of hexamers have only been reported for formate . Of particular interest is the linearly bridging water molecule (O7).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…S6 †) exhibits a typical signature for the U(IV). The different 29,48 ). The X-ray thermodiffractogram of the washed compound 1 (Fig.…”
Section: Structure Descriptionmentioning
confidence: 99%
“…40,41 Such clusters were also characterized in the solid-state for the heavier 5f elements, such as Np(IV) 40,42 or Pu(IV). 40,[43][44][45][46] It has been also reported that monotopic ligands may also act as a bidentate linker between isolated [UO 8 ] unit (with acetate) 47 or hexanuclear [U 6 O 8 ] unit with formate 48 to generate one-dimensional chain structure.…”
Section: Introductionmentioning
confidence: 99%